Studi Eksperimental Pemisah Minyak-Air Menggunakan Hidrosiklon-Bubble Generator berdasarkan Variasi Diameter Underflow - Rimbita, Trismi; Catrawedarma, IGNB.; Novita Sari, Eli; Wahid, M. Abdul; Fiveriati, Anggra (Jurnal Rekayasa Mesin, 2024)
Oil and water are two liquids that are often usedby both the public and industrial companies. Mixing oil and water need to be separated in various industries such as waste processimg, oil and gas production, and other industrial processes. Hydrocyclone is a separation method with the principle of sparation based on specific gravity which utilizes centrifugal fore by adding a bubble generator to the input section and adding variations in the underflow diameter. This research aims to analyze the performance of a hydrocyclone bubble generator based on underflow variations as oil-water separation. This bubble generator is used to make it easier to suck in air. The variations in underflow diameter used are 10mm, 15mm and 20mm. This research was carried out inject a mixture of oil and water into a hydrocyclone system as a sparation medium. The air flow injeted into the bubble generator uses air flow variations of 0.1, 0.6 and 1.2 lpm (liters/minute). From the research that has been carried out, the results show that the larger the underflow opening, the greater the pressure in the underflow, so that the underflow pressure drop is greater. The smaller the underflow opening, the greater the overflow pressure, so the overflow pressure drop is greater. The greater the input air flow, the greater the difference in underflow and overflow pressure drop. The smaller the valve opening, the lower the efficiency of oil separation in overflow and the greater the efficiency in underflow. The highest efficiency results on overflow are 88.6%.